Activation of AKT via a dual mechanism enhances the susceptibility of melanoma cells to glucose deprivation - Guang-xi Yang; De-liang Peng; Lin Chen; Yu Qian; Le He; Xiao-yan Chen; Wen-bin Hong; Cai-ming Wu; Hang-zi Chen (Cell Death and Disease)
Abstract Protein kinase AKT plays a broad role in promoting energy production in nutrient-rich environments. However, its roles under metabolic stress remain elusive. Herein, we demonstrate a dual mechanism for AKT activation during glucose deprivation. On one hand, glucose deprivation leads to increased levels of ADP and NADP+, which directly bind to spleen tyrosine kinase (SYK) and induce a conformational alteration of SYK, resulting in self-activation. The activated SYK further triggers PI3K-dependent activation of AKT. On the other hand, elevated ROS upon glucose deprivation promotes oxidative dimerization of PDK1, thereby facilitating the recognition and activation of AKT. In melanoma cells, AKT plays a critical role in elevating ROS levels and inducing cell death during glucose deprivation. Overall, this study not only establishes a novel connection between energy insufficiency and AKT activation via a dual mechanism but also provides insights into the role of AKT in sensitizing cells to metabolic stress.